DIAGNOSTIK KESULITAN BELAJAR MATEMATIKA SISWA KELAS X 2 UPTD SMA NEGERI 5 SINJAI PADA MATERI EKSPONEN - A. Rezky pratiwi; A. Mutahharah; Fahmita Sari; Irmayanti Irmayanti; fitriani fitriani (Universitas Islam Negeri Imam Bonjol Padang, 2022)
This study aims to determine the types of learning difficulties experienced by students in exponential material on the subject matter of rank forms and root forms. The type of research used in this study is Descriptive with a Qualitative approach. The subjects in this study were two class X 2 students at UPTD SMA Negeri 5 Sinjai. The research sampling technique used is purposive sampling. Taking two students as a sample with consideration of students who have moderate mathematical skills and good communication skills. The data collection techniques in this study were in the form of tests and interviews. Qualitative data analysis techniques in this study, namely: data reduction, data presentation, and drawing conclusions. The results showed that the learning difficulties experienced by the subjects were the same, namely errors in the process of solving questions.